1998
DOI: 10.1097/00002030-199801000-00010
|View full text |Cite
|
Sign up to set email alerts
|

A birth cohort analysis of AIDS in Europe

Abstract: Overall, AIDS incidence among cohorts born in 1965 and after is about the same level (homo-/bisexual men, IDU) or higher (heterosexual contact cases) than older cohorts when these were in the same age range. Rates of increase of AIDS incidence curves suggest reduced HIV transmission amongst the most recent cohorts of homo-/bisexual men and IDU, but among young heterosexuals the epidemic is still expanding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1998
1998
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…It has been known that the SDF1 - 3 ′ A mutation could result in increased SDF1 production, resulting in delayed infection due to the strong competition with the CXCR-4 chemokine receptor. Other groups, however, did not observe a similar inhibitory effect, but instead reported that patients who were homozygous for the SDF1 - 3 ′ A variant had more-rapid disease progression [28-31]. Importantly, the frequency of the SDF1 - 3 ′ A mutation varies in different ethnic populations [32].…”
Section: Introductionmentioning
confidence: 99%
“…It has been known that the SDF1 - 3 ′ A mutation could result in increased SDF1 production, resulting in delayed infection due to the strong competition with the CXCR-4 chemokine receptor. Other groups, however, did not observe a similar inhibitory effect, but instead reported that patients who were homozygous for the SDF1 - 3 ′ A variant had more-rapid disease progression [28-31]. Importantly, the frequency of the SDF1 - 3 ′ A mutation varies in different ethnic populations [32].…”
Section: Introductionmentioning
confidence: 99%